487 Instrumental evaluation of mild cognitive decline in hypertensive patients: the role of transcranial doppler. (8th December 2021) - Junior Ferruzzi, Germano; Visco, Valeria; Loria, Francesco; Donnarumma, Sofia; Galasso, Gennaro; Iaccarino, Guido; Vecchione, Carmine; Ciccarelli, Michele
Abstract: Aims: Hypertension is a known risk factor for stroke and vascular dementia. Recent studies have also shown that arterial hypertension represents a clear risk factor for mild cognitive decline and its evolution into Alzheimer's disease. Really, mild cognitive decline significantly compromises the patient's quality of life, reducing compliance with therapy and increasing mortality and hospitalization. Diagnosis of dementia is challenging and requires both ruling out potentially treatable underlying causes and ruling in a diagnosis of dementia subtype. Currently, this diagnosis is based on the execution of second-level investigations (e.g. neuroimaging), that are expensive and not always available. For this reason, we analysed a population of hypertensive patients without atrial fibrillation and/or cerebrovascular and/or neurodegenerative diseases, with the aim of verifying the existence of an association between cognitive impairment and flows on the middle cerebral artery (MCA). Methods: We considered 33 hypertensive patients (age 64.90 co1.40 years; 72% male). Specifically, we considered anthropometric, clinical, laboratory, and echocardiographic parameters. Also, we administered: an accurate, sensitive, and specific screening test (QMCI) for the assessment of intermediate cognitive decline (MCI), which explores spatial and temporal orientation, registration, delayed recall, clock design, logical memory and verbal fluency in a concise time (5 min—score 0–100); a compliance questionnaire (Morisky medication adherence scale); a questionnaire on nutritional status (MNA). Finally, we recorded transcranial Doppler flows on the MCA. Results: There is no QMCItot score compatible with dementia (<20) among the patients analysed. A statistically significant inverse association emerged between total QMCI score and Morisky score ( P  < 0.0001); in addition, the analysis of the different sections of the QMCI questionnaire showed: an inverse relationship between the Morisky score and the clock test ( P 0.013), delayed recall ( P 0.024) and logical memory ( P 0.028). By comparing the Doppler velocities sampled on the MCA with QMCI scores, a statistically significant inverse relationship was found between mean flow velocity and orientation at QMCI ( P 0.023), between PSV and orientation ( P 0.017) and between EDV and orientation ( P 0.049) ( Figure ). Conclusions: In conclusion, our study demonstrates for the first time the existence of a significant association between the QMCI and the sampling of the MCA at the ultrasound Doppler. Studies on a larger population will be needed to confirm this association and to test the translational relevance, in particular to tailor therapeutic approach in patients with abnormal MCA Doppler.